Rynek jako narzędzie wolności i jako pole walki o panowanie - Ząbkowicz, Anna (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2004)
The paper outlines the fundamental division among the theorists who professionally deal with market economy, over the issue whether market economy promotes an individual’s freedom. The discrepancy starts with the very notion of freedom, next there is no consent whether there is a relation between freedom and economic liberty, etc. Since these philosophical issues cannot be solved by the most prominent minds in this field, the author of the paper is not to be expected to offer the ultimate answer, either. However, it can be agreed that the beginning of capitalism was accompanied by progress towards freedom, towards individuals rejecting the influence of the Church, the guild and secular authority. Although the new economy, which was coordinated by market forces, marked a significant progress towards liberty, the words of a philosopher who saw its birth remain valid: „Man is born free, yet everywhere he is in chains” (Jean-Jacques Rousseau).